Teacher Strategies in Fostering Children's Empathy through Moral Story Learning in Lower Grades - Iis Aprinawati; Nurmalina (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
This study aims to describe teachers’ strategies in fostering children’s empathy through moral story-based learning in lower elementary grades. Empathy is a crucial aspect of children’s socio-emotional development that can be nurtured through literary literacy activities. This research employed a descriptive qualitative method involving grade 1–3 teachers in a public elementary school. Data were collected through classroom observations, in-depth interviews, and analysis of instructional materials. The findings reveal three main strategies: (1) selecting moral stories relevant to children’s daily lives; (2) implementing interactive storytelling with value reflection; and (3) conducting follow-up activities such as empathetic discussions and role-playing. These strategies effectively enhance students’ social awareness, emotional understanding, and prosocial behavior in lower grades. The study recommends ongoing literary literacy training for teachers to integrate empathy values into Bahasa Indonesia learning sustainably.